(untitled) (Harmoni, 2012)
Dynamic of religious life in south Palu is normal and condusive. It is supported by some factors, that are conditioned among the people and it might be a model for other provinces. Actually the form of harmonious life has not been productive in terms of interreligion cooperation. Some most factors in creation of such good life are resilience developing for individual, family and interreligious community. This study is approached by qualitative research.